THE USE OF X-RAY FLUORESCENCE SPECTROSCOPY TO DETERMINE THE ELEMENTAL COMPOSITION OF SUBSTANCES IN THE STUDY OF BIOPHYSICS - Boychuk, Volodymyra; Kotsyubynsky, Volodymyr; Turovska, Liliia; Moiseienko, Mykola; Bandura, Khrystyna; Stynska, Viktoria; Prokopiv, Liubov; Mazurenko, Yuliia; Kuzyshyn, Myroslav (Physical and Mathematical Education, 2023)
Formulation of the problem. The central challenge addressed in this study is effectively integrating cutting-edge technologies, such as X-ray fluorescence spectroscopy, into higher education curricula, particularly within medical and pharmaceutical disciplines. The study seeks to address the pedagogical question: how can educational practices be optimized to facilitate the understanding and application of complex analytical techniques while simultaneously encouraging the development of students' critical, independent problem-solving skills?Materials and methods. Materials: various material samples (powdered, solid, liquid), X-ray fluorescence spectrometer (EXPERT 3L model), and assorted soil samples for elemental composition study. Methods: Theoretical Instruction: Comprehensive teaching of the theoretical principles underlying X-ray fluorescence spectroscopy using a blend of lectures, readings, and discussions. Practical Laboratory Work: Encouraging hands-on, independent laboratory work using the EXPERT 3L X-ray fluorescence spectrometer, enhancing the understanding of practical applications. Data Analysis Training: Instruction on analyzing data from the spectrometer, improving both qualitative and quantitative analysis skills. Self-Directed Learning: Encouraging initiative, creativity, and self-sufficiency among students by promoting independent problem-solving activities.Results. Successful development and implementation of laboratory practicals titled into the training of future medical professionals. Enhanced Student Engagement and Skill Development: The practical session had a significant impact on stimulating students' intellectual activity, fostering logical thinking skills, establishing inter-thematic and inter-subject connections, and promoting creative competencies. Formulation of Subject and Professional Competencies: The experimental class successfully molds both subject-specific and professional skills, equipping the students with the tools necessary for their future careers.Conclusions. Integrating advanced analytical techniques, such as X-ray fluorescence spectroscopy, into the curriculum greatly enhances student engagement and understanding, contributing to theoretical knowledge and practical skill development. The experimental approach aided in establishing inter-thematic and inter-subject connections, vital for comprehensive learning in multidisciplinary fields like medical and biological physics. The results affirm that integrating practical exercises into the curriculum, especially those utilizing modern techniques, can help bridge the gap between theory and practice, fostering a deeper understanding of the subject matter. Future studies could explore other educational strategies or technologies that enhance student engagement and understanding in material analysis.
Keywords: Experiential Learning; Active Learning; Professional Competencies; X-ray Fluorescence Spectroscopy; Elemental Composition Analysis; Laboratory Practical Work; Student Engagement; Interdisciplinary Connections